Impact of Frontline Demonstrations on yield of soybean under rainfed condition in Marathwada region of Maharashtra: Impact of Frontline Demonstrations on yield of soybean under rainfed condition in Marathwada region of Maharashtra - S P MEHTRE; R S JADHAV; V R GHUGE; M J PATANGE (Journal of Oilseeds Research, 2023)
The frontline demonstrations of soybean were conducted by AICRP on soybean, VNMKV, Parbhani during the kharif season 2019-20 under the guidance of IISR, Indore by adopting new cultivars of Soybean viz., MAUS 162, MAUS 158 and MAUS 612 along with applying improved package of practice verses farmers practice in soybean cultivation. The productivity and economic returns of soybean in improved technologies (IT) were calculated and compared with the farmer’s practices (FP). Findings of this experiment indicated that different cultivars of soybean recorded higher gross returns, net return and benefit cost ratio in improved technologies as compared to the plots where farmers using traditional practices in their cultivation. The average soybean yield in FLD plot was 24.30 per cent (Range: 23.52 to 25.22 %) higher than the framers practice field. It is suggested that location-specific improved production technology with improved variety would be needed to bridge the productivity gap of soybean in Marathwada region of Maharashtra.